Foliar Application and Translocation of Radiolabeled Zinc Oxide Suspension vs. Zinc Sulfate Solution by Soybean Plants - Anita Beltrame; João Paulo Rodrigues Marques; Mariana Ayres Rodrigues; Eduardo de Almeida; Márcio Arruda Bacchi; Elisabete Aparecida De Nadai Fernandes; Rafael Otto; Hudson Wallace Pereira de Carvalho (Agriculture)
The present study employed a 65Zn radioactive isotope as a tracer to investigate the foliar uptake and distribution patterns of ZnO concentrated suspension- and ZnSO4 solution-sprayed on soybean plant leaves. The radiolabeled foliar treatments were sprayed on the leaves at V4 and V8 phenological stages. The radioactivity of 65Zn in the leaves, roots, stems, and pods was determined using γ-ray spectrometry. After the first foliar spray, V4, the partition of radiolabeled Zn in plants treated with ZnO and ZnSO4 was 99.22% and 98.12% in treated leaves, 0.15% and 0.39% in stems, 0.16% and 0.29% in roots, and 0.47% and 1.19% in newly expanded non-treated leaves, respectively. After two sprayings, V4 and V8, the partition of radiolabeled Zn in plants treated with ZnO and ZnSO4 was 92.56% and 92.18% in treated leaves, 0.92% and 0.70% in stems, 0.52% and 0.39% in roots, 5.60% and 6.15% in newly expanded non-treated leaves, and 0.43% and 0.61% in grains, respectively. The total fraction translocated from the application tissue was 0.79% and 1.91% for ZnO and ZnSO4, respectively, after 12 days and 8.03% and 8.48% for ZnO and ZnSO4, respectively, after 72 days. An anatomical analysis revealed that plants cultivated in a nutrition solution with 10% ionic strength had 63% fewer stomata, and the xylem vessels were 63% smaller compared to plants grown in a solution with 100% Zn ionic. One can conclude that after a short period, 12 days, the absorption and translocation of ZnSO4 was higher and faster than ZnO, and after the long period, 72 days, their performance was similar.